Future Arctic : field notes from a world on the edge - Struzik, Edward, 1954- (Island Press, 2015)
In one hundred years, or even fifty, the Arctic will look dramatically different than it does today. As polar ice retreats and animals and plants migrate northward, the arctic landscape is morphing into something new and very different from what it once was. While these changes may seem remote, they will have a profound impact on a host of global issues, from international politics to animal migrations. In Future Arctic, journalist and explorer Edward Struzik offers a clear-eyed look at the rapidly shifting dynamics in the Arctic region, a harbinger of changes that will reverberate throughout our entire world. A unique combination of extensive on-the-ground research, compelling storytelling, and policy analysis, Future Arctic offers a new look at the changes occurring in this remote, mysterious region and their far-reaching effects.